2022
DOI: 10.1002/smll.202107594
|View full text |Cite
|
Sign up to set email alerts
|

CeO2 Functionalized Cobalt Layered Double Hydroxide for Efficient Catalytic Oxygen‐Evolving Reaction

Abstract: Water splitting to produce hydrogen is an effective means to alleviate the energy crisis. The anodic oxygen‐evolving reaction (OER) limits the overall efficiency due to its high energy barrier. To address this, layered double hydroxides (LDHs) with high catalytic activities have been widely studied, especially those modified with CeO2, either bound to the surface or doped into interior. However, experimental evidence for the atomic‐level understanding of the mechanism for the enhanced catalytic performance is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Deconvolution of Co 2p 3/2 and Co 2p 1/2 peaks confirm the existence of Co 3+ and Co 2+ species in LaCoO 3 (Figure 2e). [42] The La 3d spectra of LaCrO 3 , LaMnO 3 , LaFeO 3 and LaCoO 3 all show a pair of spin orbital peaks at 834.1 and 850.5 eV, respectively (Figure S6, Supporting Information). [33] These results are consistent with the previously reported studies, verifying the successful preparation of LaCrO 3 , LaMnO 3 , LaFeO 3 , and LaCoO 3 perovskites.…”
Section: Resultsmentioning
confidence: 99%
“…Deconvolution of Co 2p 3/2 and Co 2p 1/2 peaks confirm the existence of Co 3+ and Co 2+ species in LaCoO 3 (Figure 2e). [42] The La 3d spectra of LaCrO 3 , LaMnO 3 , LaFeO 3 and LaCoO 3 all show a pair of spin orbital peaks at 834.1 and 850.5 eV, respectively (Figure S6, Supporting Information). [33] These results are consistent with the previously reported studies, verifying the successful preparation of LaCrO 3 , LaMnO 3 , LaFeO 3 , and LaCoO 3 perovskites.…”
Section: Resultsmentioning
confidence: 99%
“…As reported, the Ce species in CeO 2 includes two convertible oxidation states: Ce 4+ and Ce 3+ , which are often accompanied by the formation of oxygen vacancies. 20 As shown in Figure S3, the crystal structure of the (111)/ (100)CeO 2−x photocatalyst is not destroyed under the reduction treatment. The electron energy loss spectrum (EELS) of (111)/(100)CeO 2−x in Figure S4 also proves the coexistence of Ce 3+ and Ce 4+ .…”
Section: Structure Features Of As-prepared Ceria-basedmentioning
confidence: 90%
“…Similarly, CeO 2 (110) presents the highest possibility for FLPs construction ( Huang, 2016 ; Zhang et al, 2017 ). Many studies have proposed that FLPs constructed on defective ceria possess high activities for many small-molecule activation (such as, H 2 , NO, CO 2 ) ( Mo et al, 2015 ; Stephan and Erker, 2015 ; Huang et al, 2018 ; Li J. et al, 2021 ; Li et al, 2022 ; Zhang et al, 2022 ; Zou et al, 2022 ). Qu’s group have explored the adsorption and activation of CO 2 on CeO 2 (110) surface by DFT calculations and found that CO 2 can be easily activated on defective CeO 2 and further activated on FLPs because of the more negatively charged oxygen of CO 2 , when compared to CO 2 on an ideal CeO 2 (110) surface ( Figure 6A ) ( Zhang et al, 2019 ).…”
Section: Electronic Properties Of Ceo 2 -Based Nan...mentioning
confidence: 99%
“…Meanwhile, CeO 2 /Co 3 O 4 interface nanotubes with a Ce/Co ration of 2:20 can achieve an ultrahigh mass activity with a current density of 128.6 A·g −1 at a given overpotential of 340 mV and enable an OER Faradaic efficiency of ∼99%. Li et al (2022) have reported a very different conclusion on the valence of active Co ions by using CeO 2 nanoparticles anchored Co layered double hydroxide (LDH) as a catalyst. They deemed that the Co 3+ with strong Lewis acidity helps the binding of OH − and thus benefiting the formation and transformation of oxygen-containing intermediates by forming CoOOH active species ( Li Z. et al, 2021 ).…”
Section: Applications In Energy Storage and Conversionmentioning
confidence: 99%